Atomic Physics for Everyone - Raven, Will (Springer Nature, 2024)
This open access textbook introduces beginning undergraduate students and high school students to the world of quantum mechanics and atomic spectroscopy. Requiring no previous knowledge of physics and no math beyond basic algebra and sines and cosines, this book focuses on concepts to make the excitement of atomic physics more accessible for learners than ever before. It comes replete with learning goals, exercises and solutions, and an optional experimental component, making this text readily adoptable for both the classroom and the undergraduate lab. The book takes the reader on a lively and engaging tour through topics at the forefront of current science, including photons, quantum numbers, atomic energy levels, some different spectroscopy techniques, electronic structure, atomic notation, angular momentum, hyperfine structure, isotope shifts, the strong force, an introduction to the Standard Model of Particle Physics, and more. This is an open access book.